2008
DOI: 10.1080/13693780701885636
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase activity of yeasts from wild birds and possible implications for human disease

Abstract: Over the last decades, reports on yeast infections in humans have increased especially with respect to immunocompromised individuals. Phospholipases are enzymes which may be associated with pathogenic processes caused by opportunistic yeasts. Phospholipase activity (ph.a.) was investigated in 163 isolates of 13 species of yeasts. A total of 133 isolates were obtained through the screening of a total of 768 cloacae of wild birds (Group I: 182 birds of prey; Group II: 165 passeriformes and Group III: 421 other w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 32 publications
1
28
1
4
Order By: Relevance
“…Later, Cafarchia and collaborators investigated the phospholipase activity in a collection of 163 yeast isolates recovered from pigeon cloacae and droppings (22). Biochemical and morphological tests identified 13 species among these isolates, of which 14 isolates were identified as T. beigelii.…”
Section: Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Cafarchia and collaborators investigated the phospholipase activity in a collection of 163 yeast isolates recovered from pigeon cloacae and droppings (22). Biochemical and morphological tests identified 13 species among these isolates, of which 14 isolates were identified as T. beigelii.…”
Section: Enzymesmentioning
confidence: 99%
“…These organisms can be found in substrates such as soil, decomposing wood, air, rivers, lakes, seawater, cheese, scarab beetles, bird droppings, bats, pigeons, and cattle. In humans, these fungal species occasionally are part of the gastrointestinal and oral cavity microbiota and can transiently colonize the respiratory tract and skin (22,60,68,76,101,108,170,186,188,189). Recently, Silvestre et al found that 11% of their 1,004 healthy male volunteers were colonized by Trichosporon species on their normal perigenital skin (scrotal, perianal, and inguinal sites of the body) (165).…”
Section: Introductionmentioning
confidence: 99%
“…2 They belong to the human microbiome, as colonizers of the gastrointestinal and oral cavities, male perigenital skin (scrotal, perianal, and inguinal sites of the body) and temporarily inhabiting the respiratory tract and skin. [3][4][5][6][7][8][9][10][11][12] It is not clear how Trichosporonosis can be acquired, but the following possibilities can be envisaged: (i) poor hygiene, (ii) bathing in contaminated water, (iii) sexual transmission, (iv) hair humidity and the length of the scalp hair (more specifically in the case of acquiring white piedra), (v) gastrointestinal colonization and further translocation throughout the gut (deep-seated infections), and (vi) exogenously acquired through a percutaneously inserted intravascular catheter via colonized skin. [13][14][15][16][17][18] In spite of the fact that Trichosporon spp are probably the second or third most common non-Candida yeast infections causing invasive disease in patients with hematological cancer, there are few reports related to virulence factors of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Leveduras do gênero Candida também são encontradas como parte da microbiota do trato digestivo de diversas aves, tais como pombos, perus, aves de rapina, aves migratórias, aves industriais, drentre outras (CAFARCHIA et al, 2006, FULLERINGER et al, 2006CAFARCHIA et al, 2008). De acordo com CARFACHIA et al, (2006), as aves transportam em sua cloaca leveduras potencialmente patogênicas, sendo capazes de disseminar esses fungos no ambiente, o que é um problema quando se trata de aves criadas em confinamento (FULLERINGER et al, 2006).…”
Section: Importância De Candida Spp Na Medicina Veterináriaunclassified
“…Alguns fatores estão relacionados com essa característica de patogenicidade, tais como: capacidade de crescer a 37°C; pleomorfismo, cujo papel é importante nos processos iniciais de invasão tecidual; produção de alguns metabólitos, que podem desencadear manifestações alérgicas do tipo imediato e tardio; produção de adesinas e de enzimas hidrolíticas, tais como proteinases e fosfolipases, consideradas fatores importantes de virulência do gênero e sendo produzidas pelas mais variadas espécies de Candida (SIDRIM & ROCHA, 2004;KUMAR et al, 2006;CAFARCHIA et al, 2008). Na Medicina Veterinária, são fatores predisponentes a infecções por Candida: idade, presença de doenças autoimunes, Diabetes mellitus, uso de corticosteroide, antibioticoterapia, cateterismo venoso e urinário e administração de nutrição parenteral (VELASCO, 2000;HESELTINE et al, 2003;MORETTI et al, 2004;KIVARIA & NOORDHUIZEN, 2007).…”
Section: Como Patógenounclassified